Removal trends of sulfonamides and their ARGs during soil aquifer treatment and subsequent chlorination: effect of aerobic and anaerobic biodegradation. Issue 9 (10th June 2020) - Qin, Kena; Chen, Yan; Li, Jianju; Xue, Chonghua; Wei, Liangliang; Song, Xugang; Ding, Jing; Zhao, Qingliang
Abstract : Soil aquifer treatment significantly decreased the SA concentration in recharged synthetic water and aerobic biodegradation played a great role. Abstract : Sulfonamides (SAs), the most widely used antibiotics, are frequently detected in wastewater treatment plant effluent. In this study, the removal trends of four typical SAs (sulfadiazine (SDZ), sulfamethoxazole (SMX), sulfapyridine (SPD) and sulfamethazine (SMT)) in lab-scale soil aquifer treatment (SAT) systems, as well as their chlorination behaviors, were evaluated. As much as 68.2–88.9% of SAs in the synthetic water samples (10 μg L −1 initial concentration) were efficiently removed during steady-state operated SAT, which was the highest for sulfadiazine and lowest for sulfamethazine. Specifically, aerobic biodegradation in the soil played a great role in SA removal and contributed 55.7%, 57.8%, 61.1% and 74.0% to SMT, SMX, SPD and SDZ removal, respectively. Cleavage of the aniline group and desulfation of the SAs were the main pathways for their degradation during soil degradation. Subsequent chlorination could partially eliminate the SAs in the SAT effluent but not entirely, with a removal rate of 8.21% for SDZ, 7.45% for SMX, 14.21% for SPD, 16.52% for SMT, respectively. Electrophilic substitution of the aniline group and reaction with desulfation products produced different chlorinated by-products. The intermediates of the SAs originating from the SAT biodegradation contributed to the formation of chlorinated by-products and antibiotic resistance genes (ARGs), especially for organic compounds generated under aerobic biodegradation conditions. Taken together, our findings demonstrated that the abundant existence of SAs in the recharging samples would lead to health concerns due to the high concentrations of ARGs and precursors of chlorination by-products, especially with traditional chlorination processes.